Cooled radiofrequency ablation of cervical medial branches for treatment of facetogenic pain - Nithya Dinesh; Rajat Gupta; Deep Divanshu Lall; Ashu Kumar Jain (Indian Journal of Pain, 2022)
In cervical spine, the anatomical course of medial branch in significantly different and thermal radiofrequency ablation (RFA) of the cervical median branch though proven effective is technically challenging. Cooled RFA (CRFA) is a newer revolutionary technique that creates a larger spherical lesion and thus compensates for the anatomical variability of the medial branches in the cervical spine. Our case report is aimed to discuss the technique of CRFA for the treatment of cervical facetogenic pain. Right C2–C5 medial branch CRFA was done under fluoroscopic guidance under monitored anesthesia care using 17G with 75 mm length and 2 mm active tip cooled radiofrequency cannula. After 8 weeks of follow-up, the patient reported 80% pain relief.